La Commande de la Machine Asynchrone - HaneneSatour (My University, 2025)
This thesis focuses on the control of the asynchronous machine and is structured into three chapters. The first chapter presents the asynchronous machine and its modeling. The second chapter addresses indirect vector control based on rotor flux orientation, incorporating classical PI controllers whose gains are optimized using genetic algorithms. Finally, the third chapter implements the previously developed concepts through simulations in MATLAB/Simulink, enabling an analysis of the performance of the proposed control strategy. ---------------------------------------------------------------------------- تتناول هذه المذكرة موضوع التحكم في الآلة غير المتزامنة، ويتكون من ثلاثة فصول. يقدم الفصل الأول الآلة غير المتزامنة ونمذجتها. أما الفصل الثاني، فيتناول التحكم الاتجاهي غير المباشر القائم على توجيه تدفق الدوار، من خلال دمج منظمات PI التقليدية التي تم تحسين معاملات التحكم فيها باستخدام الخوارزميات الجينية. وأخيرًا، يطبق الفصل الثالث المفاهيم المطورة سابقًا من خلال محاكاة باستخدام برنامج (MATLAB/Simulink)، مما يسمح بتحليل أداء إستراتيجية التحكم المقترحة ---------------------------------------------------------------------------- Ce mémoire porte sur la commande de la machine asynchrone et s’articule en trois chapitres. Le premier chapitre présente la machine asynchrone ainsi que sa modélisation. Le second traite de la commande vectorielle indirecte basée sur l’orientation du flux rotorique, en intégrant des régulateurs PI classiques dont les gains sont optimisés à l’aide d’algorithmes génétiques. Enfin, le troisième chapitre met en œuvre les concepts développés précédemment à travers des simulations sous MATLAB/Simulink, permettant d’analyser les performances de la stratégie de commande proposée
Keywords: Asynchronous machine – Indirect vector control – PI controller – Gain optimization – Genetic algorithms.; الآلة غير المتزامنة - التحكم الاتجاهي غير المباشر - منظم PI - تحسين المعاملات - الخوارزميات الجينية; Machine asynchrone- commande vectorielle indirecte -régulateur PI-optimisation des gains- algorithmes génétiques